Analisis Dilema Utang Luar Negeri Dan Kemandirian Fiskal: Strategi Pembiayaan Pembangunan Di Negara Berkembang Periode 2020-2025 - Zebua, Agusman Niat Berkat (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This study examines the complex relationship between dependence on foreign debt and accelerated economic development. Amidst low tax ratios, many developing countries use debt as a financing gap-filling instrument. Using a desk study and secondary data analysis for the 2020-2025 period, the study shows that while debt can stimulate short-term growth through infrastructure development, the high interest burden risks creating a debt overhang that hinders fiscal independence. Digitizing the public financial system is proposed as a key strategy to strengthen domestic revenues.